CHARACTER EDUCATION IN ELEMENTARY SCHOOLS: THE ROLE OF SCHOOL MANAGEMENT IN RESPONDING TO CHILDREN'S SOCIAL AND MORAL ISSUES IN THE MODERN ERA - Sudirman, Sudirman; Hefniy, Hefniy; Yaqin, Ainol (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyse the integration of character education in teaching activities, managerial responses to social and moral changes in children in the modern era, and the synergy between school management and character education in rural areas. The research was conducted at SD Negeri Kedawung II, in Kuripan District, Probolinggo Regency, in Krajan Hamlet, Kedawung Village. The research method used is qualitative with a descriptive approach, aiming to describe the phenomena that occur and analyse the challenges faced by the school in managing character education amidst existing social dynamics. Data were collected through direct observation and in-depth interviews with the school principal, teachers, and several parents. The results show that the integration of character education into teaching activities at SD Negeri Kedawung II has been successfully implemented by reinforcing moral and ethical values in every aspect of school life. Managerial responses to social and moral changes in children in the modern era are reflected in the school's efforts to adapt to the negative influences of technological development and globalisation on students' character. The synergy between school management and character education has proven effective despite significant challenges, particularly regarding limited resources and external cultural influences. The impact of social dynamics in rural environments also affects the formation of children's character, where local values play a crucial role in the educational process. This study underscores the importance of the role of school management in creating an environment that supports the formation of children's character in the modern era.Keywords: Character Education, Role, Management